Conflict and classification: the communicational approach of the Palo Alto school applied to three novels of Anthony Trollope - VanIngen, Mary-Jo (Europäische Hochschulschriften / 14, 1991)
Klappentext: The dialogues of the mid-Victorian novelist, Anthony Trollope, are particularly permeable to modern psycholinguistic terminology as used by the Palo Alto school, especially by Paul Watzlawick in Pragmatics of Human Communication. We have classified Trollope novels into pleasant and unpleasant, using Barchester Towers and He Knew He was Right as respective examples of normogenic personal and social conflict, and schizophrenia-induced hubris. We have cast seven dialogues in graphic form: first according to the semiotic system by Carlos E. Sluzki and Janet Beavin, and then in the more comprehensive form of Klaus Muderbach's Interaction Notation. The question is posed whether a semiotic notation can show differentiation between psychotic and normogenic behavior, with reflections on how to define each.
Includes bibliographical references (p. 323-327)
Keywords: Hochschulschrift; Double-bind-Hypothese; Trollope, Anthony / The prime minister; Trollope, Anthony / Barchester Towers